1. The problem statement, all variables and given/known data The problem is attached. The correct answers are: f'(1) = -68 ∂g/∂s(1, 1) = 14 ∂g/∂t(1, 1) = -136 2. Relevant equations Differentiation and partial differentiation. 3. The attempt at a solution I'm at the f'(1) part. I differentiated each component of F(2 – 3t + 2t^2, 19 – 27t + 9t^2, -4 + 3t + 2t^2) to get f'(t) = F(-3 + 4t, -27 + 18t, 3 + 4t) and then f'(1) = F(1, -9, 7). I'm not entirely certain if what I did is correct so far. If it is, what do I do next? If I omitted something important, tell me. Any help in solving this problem would be greatly appreciated! Thanks in advance!